2-Amino-4-methylpyridinium 3-chlorobenzoate - Madhukar Hemamalini; Hoong-Kun Fun (Acta Crystallographica Section E, 2010)
In the title salt, C6H9N2+·C7H4ClO2−, the 2-amino-4-methylpyridinium cation is almost planar, with a maximum deviation of 0.010 (1) Å. In the crystal, the protonated N atom and the 2-amino group of the cation are hydrogen bonded to the carboxylate O atoms of the anion via a pair of N—H...O hydrogen bonds, forming an R22(8) ring motif. The ion pairs are further connected via N—H...O and C—H...O hydrogen bonds, forming a two-dimensional network parallel to the bc plane.